Death from Fat Embolism after Lipectomy in a Patient with Madelung's Disease - Xing-An Yang; Teng-Fei Yang; Fu Zhang; Jiang-Wei Kong; Zi-Lin Meng; Xin-Biao Liao; Pei-Yu Liang; Dong-Ri Li (Wolters Kluwer Medknow Publications, 2024)
A 56-year-old man with a long history of alcoholism and a palpable raised mass about 23 cm × 12 cm in size on his neck was diagnosed with Madelung's disease (MD); the patient also had hyperuricemia. On day 1, he underwent neck lipoma tissue resection and suddenly had dyspnea 9 h after the operation, which was followed by cardiac arrest. After heart rate resuscitation, he developed a heartbeat, but he remained in a coma and died 9 days after the operation. No obvious pathological tracheal compression from a hematoma was observed while evaluating the patient's neck on autopsy. On microscopy, the patient had an extensive pulmonary fat embolism, partial alveolar septal rupture and hemorrhage, and fat particles, and there was extensive infiltration of macrophages, which had phagocytosed fat particles, in the alveolar cavity. There was also evidence of pulmonary infection and hypoxic-ischemic encephalopathy. The cause of death was postoperative pulmonary fat embolism resulting in pneumonia and central nervous system injury. This is the first report of a patient with MD who died of a fatal pulmonary fat embolism after neck lipoma tissue resection. Medicolegal experts and clinicians should pay sufficient attention to this case.